(untitled) (Tanzania Journal for Population studies and Development, 2018)
In the digital governance era, government institutions and civic organisations have innovated spaces for engaging with ordinary citizens in the governance of services. Digital information and communication technology penetrate and reshapes all walks of life from collective participation to timely and quick auditing and sharing of information of the status of social services. Yet, little is documented regarding mobile participation (m-participation) initiatives in monitoring social services and citizengenerated data in Tanzania. This article is an exploratory work that identifies and maps citizen m-participation projects in the monitoring of social services. Besides, it highlights how e-services cases are in line with the current sustainable development goals (SDGs). In this line, we argue that mobile phone technology is a tool for empowering citizens to participate in governance of social services. The paper deploys document and web analysis to identify and highlight citizen m-participation projects. The findings indicate that mobile technology amplifies the opportunity for citizen participation in governance processes given the high penetration rate of mobile phones for texting and calling, compared to online web-based technology that depend on the internet connection which is still scanty.